Alberdi y el Brasil en los escritos del Ciclo de la Guerra del Paraguay: las funciones de una visión en bloque - Lucila Pagliai (Centre de Recherches sur les Mondes Américains, 2009)
The Empire of Brazil has a significant place in Juan Bautista Alberdi’s published and unpublished works. This paper studies the mode of inscription of Brazilian presence in Alberdi’s  writings about the Paraguayan War, specifically in the letters sent to the diplomat Gregorio Benites, representative of Paraguay in Europe. It analyzes these papers as a text policy that establishes a unique, monolithic image of the Second Empire and its ideologues, aiming at producing a pragmatic effect in favour of the Paraguayan cause on policy makers and public opinion in Europe and the United States.